Die Rechtsprechung des Bundesverfassungsgerichts zum Strafvollzug und Untersuchungshaftvollzug - Lübbe-Wolff, Gertrude (Nomos Verlagsgesellschaft mbH & Co. KG, 2016)
In Germany, legislation concerning the treatment of prisoners and detainees in forensic psychiatric institutions, as well as the interpretation of the relevant law have to a large extent been shaped by the case-law of the Federal Constitutional Court. The author, from 2002 to 2014 Associate Justice on the Federal Constitutional Court, presents a comprehensive survey of that case-law on the basis of extracts from decisions, covering general principles - concerning, for example, security, resocialisation, the implementation of preventive detention, and the admissible reach of privatisations - as well as all kinds of living conditions and measures to which prisoners and other detainees may or may not be subjected, and the relevant constitional requirements concerning judicial protection.